Employment characteristics and cause‐specific mortality at automotive electronics manufacturing plants in Huntsville, Alabama. Issue 4 (21st February 2019) - DeBono, Nathan; Richardson, David; Keil, Alex; Kelly‐Reif, Kaitlin; Robinson, Whitney; Troester, Melissa; Marshall, Stephen
Abstract: Background: This study was carried out in response to worker concerns over their exposure to lead solder and chlorinated solvents at automotive electronics manufacturing plants in Huntsville, Alabama. Methods: A study of 4396 United Autoworkers members ever‐employed at the plants between 1972 and 1993 was conducted with mortality follow‐up through 2016. Poisson regression was used to estimate mortality rate ratios (RR) according to employment characteristics, including calendar period of employment. Results: Pre‐1977 hires exhibited elevated adjusted rates of all‐cause (RR, 1.29; 95% confidence interval [CI], 1.09‐1.52), cardiovascular (RR, 1.38; 95% CI, 1.03‐1.86), and digestive system (RR, 2.31; 95% CI, 1.04‐5.10) disease mortality relative to the most recent hire group (1984‐1993). Never‐ versus ever‐employment in a skilled trade job was associated with elevated adjusted rates of all‐cause, all‐cancer, and cardiovascular disease mortality. Nervous system disorder mortality was greatest among 1977‐1983 hires. Conclusions: Elevated mortality among pre‐1977 hires is consistent with worker concerns over greater exposure to hazards at the original plant building.